2007
DOI: 10.1111/j.1365-2109.2007.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different types of live and non-conventional diets in endangered clown knife fish Chitala chitala (Hamilton-Buchanan) during its early life stages

Abstract: In the present study, the growth and survival of early life stages (ELS) of Chitala chitala were studied in nylon hapa for 28 days, followed by rearing in fibreglass reinforcement plastic (FRP) tanks for a period of 30 days. Ten‐day‐old ELS of C. chitala reared in hapa were fed with three different diets namely Indian Major Carp (IMC) spawn (<8 mm), live tubifex and fresh fish eggs. In the second phase, 28‐day‐old ELS were stocked in 200‐lit FRP tank and supplied four different live diets namely live tubifex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…C. chitala is a high-priced fish for food, sport and aquarium purposes due to its rarity and delicacy ( Gopalan, Ramasastri & Balasubramanian, 2004 ; Sarkar, Deepak & Lakra, 2009 ). The population of this species has reduced considerably due to over-exploitation, habitat alteration, pollution and related anthropogenic pressure on their natural habitats and thus, is categorized as near threatened (NT) by International Union for Conservation of Nature ( Swain et al, 2021 ) though it was earlier categorized as endangered (EN) ( Ayyappan, Raizada & Reddy, 2001 ; Sarkar et al, 2007 ). Assessment of C. chitala for the IUCN Red List of Threatened Species was most recently carried out by Chaudhry (2010) .…”
Section: Introductionmentioning
confidence: 99%
“…C. chitala is a high-priced fish for food, sport and aquarium purposes due to its rarity and delicacy ( Gopalan, Ramasastri & Balasubramanian, 2004 ; Sarkar, Deepak & Lakra, 2009 ). The population of this species has reduced considerably due to over-exploitation, habitat alteration, pollution and related anthropogenic pressure on their natural habitats and thus, is categorized as near threatened (NT) by International Union for Conservation of Nature ( Swain et al, 2021 ) though it was earlier categorized as endangered (EN) ( Ayyappan, Raizada & Reddy, 2001 ; Sarkar et al, 2007 ). Assessment of C. chitala for the IUCN Red List of Threatened Species was most recently carried out by Chaudhry (2010) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that feed acceptability is influenced by chemical stimuli created by the feed (Mackie and Adron, 1978). Moreover, feed intake largely depends on certain crucial factors, such as feed size, type, physical appearance, and attractiveness (Sarkar et al, 2007). Although fish feed contained higher protein (29.17%) than aquarium feed (18.18%), the results showed that goldfish juveniles fed fish feed had significantly lower growth (P < 0.05).…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, commercial fish pellet was used to compare the palatability with other feeds. The growth rate of fish with appropriate quality and adequate quantity of feed mostly depends on voluntary feed intake and assimilation of nutrients (Diana et al, 1988;Sarkar et al, 2007). It has been reported that feed acceptability is influenced by chemical stimuli created by the feed (Mackie and Adron, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, live feeds are conveniently used for larval feeding (Holt, 1993;People Le Ruyet et al, 1993) as it is believed that live feeds stimulate enzyme secretion resulting in good growth and survival. Tubifex is well known to increase the growth performances of different finfish species such as Chitala chitala (Sarkar et al, 2007), Clarius macrocephalus (Santiago et al, 2003) and catfish (Evangelista et al, 2005;Arslan et al, 2009). However, the regular application of live Tubifex to fish larvae is impractical for developing countries because of inconsistent supply and high price (Evangelista et al, 2005).…”
mentioning
confidence: 99%